Simple rules for sensemaking praxis: How HR can contribute to strategic change by developing sensemaking capability in organisations. (17th August 2021) - Kieran, Sarah; MacMahon, Juliet; MacCurtain, Sarah
Abstract: This paper explores how sensemaking theory offers a new perspective on HR's role during strategic change. As change in organisations today is less of a programme and more of a continuous cycle of business transformation, there has been a shift in focus to its underpinning, cognitive process of sensemaking. However, HR's role in developing sensemaking praxis in organisations is not widely researched to date. This paper addresses that gap. We draw on Eisenhardt and Sull's 'simple rules' whereby complex strategy praxis is reduced to a highly translatable, small number of key rules (2001). Through a diary study of middle managers engaging in strategic change, we investigate their real‐time, lived sensemaking praxis. We conclude that HR have a significant contribution to play in developing an organisation's sensemaking praxis through four Simple Rules of Sensemaking: (1) plan creative discourse opportunities, (2) ensure leader‐middle manager parity, (3) mutually direct sensemaking through ongoing re‐planning and re‐prioritisation, and (4) ensure leadership effort continues beyond the initiation of strategic change.